"The Original Sound": a new non-pharmacological approach to the postnatal stress management of preterm infants. (2nd November 2015) - Tandoi, Francesco; Francescato, Gaia; Pagani, Alessia; Buzzetti, Giuliano; Negri, Eva; Agosti, Massimo
Abstract>: Objective : To evaluate the effect of the exposure to "The Original Sound" (TOS), an original track composed of different sounds such as fetal heartbeat, breathing, blood flow, and ambience sounds, specifically created for this study, on physiological stability of preterm infants during a 10-d hospitalization. Methods : Thirty-four preterm infants (32–37 weeks of gestation) were randomized to receive either TOS or environmental noise. TOS was provided for a 20-min period, three times a day, using two speakers and a MP3 player placed in the cradle. Cardiorespiratory and behavioral parameters were recorded. Results : Heart rate in the treated group was positively correlated with TOS exposure, showing a significant reduction on day 2 and lower values during the first day. A decrease in RR is also recorded on day two in the TOS group, although not significant. Conclusion : This study provides preliminary evidence for short-term improvements in the physiological stability of preterm infants using TOS. Future studies are needed to investigate the potential of this non-pharmacological approach and its clinical relevance to postnatal stress management in neonatal intensive care units.